Acoustic phonetics - Stevens, Kenneth N., 1924- (MIT Press, 1998)
Content Description #Includes bibliographical references (p.) and index.
Keywords: Phonetics, Acoustic.; Phonetics.; Sound.; Phonetics; Acoustics; Phonétique acoustique.; Phonétique.; Acoustique.; phonetics.; acoustics.; LANGUAGE ARTS & DISCIPLINES -- Linguistics -- Phonetics & Phonology.; Sound; Phonetics, Acoustic; Akoestische fonetiek.; LINGUISTICS & LANGUAGE/General